Meteorological measurements and instrumentation - Harrison, R. G. (West Sussex : Wiley Blackwell, 2015)
"This book describes the fundamental scientific principles underlying high quality instrumentation used for environmental measurements"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Meteorological instruments; Meteorology -- Observations